Osteocalcin expression of platelet-rich fibrin (PRF) and platelet-rich plasma (PRP) added with hydroxyapatite (HA) in rabbit’s post extraction tooth sockets - Damayanti, Meta Maulida; Hernowo, Bethy Suryawathy; Susanah, Susi (Padjadjaran Journal of Dentistry, 2020)
Introduction: Platelets play an important role in wound healing because it is a reservoir for growth factors and cytokines which is important in bone regeneration and soft tissue healing. The purpose of this study was to compare the use of scaffolds in platelet-rich fibrin (PRF) and platelet-rich plasma (PRP) which added with hydroxyapatite (HA) in the socket healing process after tooth extraction in the value of regenerating an alveolar bone tissue. Methods: The research was conducted at biomedical laboratory Bandung Islamic University. Eighteen rabbits (Oryctolagus cuniculus) with extracted anterior and inferior teeth were divided into 2 treatment groups and 3 observation times. The tooth socket is filled with PRF (Group 1) and PRP + HA (Group 2). The observation was conducted on Day 3, Day 7 and Day 14. Immunoexpression Osteocalcin was performed to assess the healing process of alveolar bone. Data was analyzed with the SPSS software program. Analysis of normality data by Shapiro-Wilk test, homogeneity of variance with Levene's test and comparison between treatment groups with the Chi-square test. Results: Group 1 shown the average score was higher than in Group 2 with a strong category of 72.2% for Group 1 and 56.6% for Group 2. Based on statistically,  there was no difference in osteocalcin immunoexpression between Group 1 and Group 2 with the p-value>0.05. Conclusion: Regeneration of rabbit’s alveolar bone tissue by application of PRF and PRP plus HA as scaffolds have results was similar. The use of PRF in post-extraction wound recovery is a better choice because it has an easy procedure and lower cost.